(\frac{1}{5})^{x} +10\\\\\frac{1}{5}*(\frac{1}{5})^{2x}>(\frac{1}{5})^{x}+10\\\\(\frac{1}{5})^{x}=m,m>0\\\\(\frac{1}{5})^{2x}=m^{2}\\\\\frac{1}{5}m^{2}-m-10>0\\\\m^{2} -5m-50>0\\\\(m-10)(m+5)>0" alt="(\frac{1}{5})^{2x+1}>(\frac{1}{5})^{x} +10\\\\\frac{1}{5}*(\frac{1}{5})^{2x}>(\frac{1}{5})^{x}+10\\\\(\frac{1}{5})^{x}=m,m>0\\\\(\frac{1}{5})^{2x}=m^{2}\\\\\frac{1}{5}m^{2}-m-10>0\\\\m^{2} -5m-50>0\\\\(m-10)(m+5)>0" align="absmiddle" class="latex-formula">
+ - +
___________₀____________₀___________
- 5 10
//////////////////////// ///////////////////////
![1)(\frac{1}{5})^{x}<-5 1)(\frac{1}{5})^{x}<-5](https://tex.z-dn.net/?f=1%29%28%5Cfrac%7B1%7D%7B5%7D%29%5E%7Bx%7D%3C-5)
решений нет
10\\\\log_{0,2}(\frac{1}{5})^{x}>log_{0,2} 10\\\\x10\\\\log_{0,2}(\frac{1}{5})^{x}>log_{0,2} 10\\\\x